The Influence of Interactive Digital Media on Cognitive Understanding in Physical Education - Pedomanta Keliat; Satria Agus Situmorang; Roy Heber Purba; Samsul Bahari Simanullang; Setiawan Putra Zega; Satrio Gunawan Sagala (Joska: Jurnal Isori Kampar, 2025)
Objectives: Physical education has traditionally relied on conventional teaching methods, but the integration of interactive digital media presents new opportunities to enhance cognitive understanding. The evolution of digital technologies has significantly influenced educational practices, particularly in motor skill acquisition and cognitive development in physical education settings. This study aims to investigate how interactive digital media influences cognitive understanding among elementary school students in physical education, specifically examining improvements in motor skill comprehension, spatial reasoning, and movement pattern recognition. Methods: A quasi-experimental design was employed with 40 elementary school students (20 male, 20 female) from schools in Medan City, North Sumatra, Indonesia. Participants were randomly assigned to experimental and control groups. The experimental group received physical education instruction using interactive digital media, while the control group received traditional instruction. Cognitive understanding was measured through pre- and post-tests, observation checklists, and performance assessments. Results: The experimental group showed significant improvements in cognitive understanding compared to the control group (p < 0.05). Students demonstrated enhanced comprehension of movement patterns, improved spatial reasoning skills, and better retention of motor learning concepts when exposed to interactive digital media. Conclusion: Interactive digital media significantly enhances cognitive understanding in physical education among elementary students. The technology facilitates clearer visualization of movement patterns, improves student engagement, and supports more effective learning outcomes in physical education contexts.